Hubungan usia ibu saat hamil dengan stunted pada balita 24-59 bulan - Mira Sani; Tetti Solehati; Sri Hendarwati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
The maternal age on pregnancy with stunting among children of age 24 to 59 monthsBackground: Stunting is a chronic nutritional problem caused by lack of nutritional intake for a long time, resulting in a height that is shorter than the standard age (stunted). Many factors influence the incidence of stunted, including maternal, child, and social, economic and environmental factors. The mother factor that must be considered is the age during pregnancy. Age of mothers <20 years and> 35 years has a risk of stunted.Purpose: To determine the relationship between the maternal age on pregnancy with stunting among children of age 24 to 59 months in the work area health center (Puskesmas) Citeras.Methods: Descriptive correlational with a retrospective method. The population of this study were mothers who had children aged 24-59 months who had stunted in Cibunar and Kutanagara Villages. The sample was 76 respondents with total sampling technique. The instrument in this study was a questionnaire from SDKI and microtoise. Data analysis used bivariate with spearman correlation test. The study was conducted in May 2019 with ethical permits number 511 / UN6.KEP / EC / 2019.Results: The maternal age at risk in Cibunar and Kutanagara Villages is 64.5% with stunted children. By using Spearman correlation, the value is 0.001 at 1% significance level.Conclusion: There is a correlation between maternal age with stunted among children 24-59 months in the work are of Puskesmas Citeras.Keywords: Maternal age on Pregnancy; Stunting; Children of age 24 To 59 MonthsPendahuluan: Stunting merupakan masalah gizi kronis yang disebabkan oleh kurang asupan gizi dalam waktu cukup lama sehingga berakibat pada tinggi badan yang lebih pendek dari standar usianya (stunted). Banyak faktor yang mempengaruhi kejadian stunted, diantaranya faktor ibu, anak, serta sosial, ekonomi, dan lingkungan. Faktor ibu yang harus diperhatikan adalah usia saat hamil. Usia ibu yang < 20 tahun dan > 35 tahun memiliki risiko terhadap kejadian stunted.Tujuan: Mengetahui hubungan usia ibu saat hamil dengan stunted pada balita 24-59 bulan di wilayah kerja Puskesmas Citeras.Metode: Menggunakan deskriptif korelasional dengan metode retrospektif. Populasi penelitian ini yaitu ibu yang memiliki balita usia 24-59 bulan yang mengalami stunted di Desa Cibunar dan Kutanagara. Sampel 76 responden dengan teknik total sampling. Instrumen pada penelitian ini kuesioner dari SDKI dan microtoise. Analisis data menggunakan bivariat yaitu uji korelasi spearman. Penelitian dilakukan pada Bulan Mei 2019 dengan perizinan etik nomor 511/UN6.KEP/EC/2019.Hasil: Menunjukkan bahwa usia ibu saat hamil yang berisiko di Desa Cibunar dan Desa Kutanagara sebanyak 64,5% yang memiliki balita stunted. Nilai korelasi Spearman sebesar 0,001 pada taraf signifikansi 1%.Simpulan: Terdapat hubungan antara usia ibu saat hamil dengan stunted pada balita 24-59 bulan di Wilayah Kerja Puskemas Citeras.